Practical Approaches on CD30 Detection and Reporting in Lymphoma Diagnosis - Xu, Mina L; Gabali, Ali; Hsi, Eric D; Fedoriw, Yuri; Vij, Kiran; Salama, Mohamed E; Ramchandren, Radhakrishnan; O'Malley, Dennis; Wick, Mark R; Battistella, Maxime; Gru, Alejandro A (The American journal of surgical pathology, 2020)
While our understanding of the biology of CD30 in lymphoma continues to evolve, our need to detect and measure its expression at the protein level remains critically important for diagnosis and patient care. In addition to its diagnostic and prognostic utility, CD30 has emerged as a vehicle for drug targeting through the antibody-drug conjugate brentuximab-vedotin (BV). Given the numerous ways that CD30 is utilized and its emergence as a predictive/prognostic biomarker, pathologists must come to a general consensus on the best reporting structure and methodology to ensure appropriate patient care. In this manuscript, we review the indications for testing, various modalities for testing, technical challenges, pitfalls, and potential standards of reporting. The following questions will try to be addressed in the current review article: What defines a "POSITIVE" level of CD30 expression?; How do we evaluate and report CD30 expression?; What are the caveats in the evaluation of CD30 expression?